A partitioned solution algorithm for fluid flow and stress-strain computations applied to continuous casting. (May 2019) - Zhang, Shaojie; Guillemot, Gildas; Gandin, Charles-André; Bellet, Michel
Abstract: Continuous casting is currently the main industrial process for steel production. Since long time, industries search for efficient simulation methods, by which macrosegregation and deformation induced cracks can be predicted. As a first step this requires achieving concurrent simulation of fluid flow and stress-strain. Therefore, a partitioned solution algorithm is developed for such simulation with application to continuous casting. Liquid flow induced by natural convection or filling step, solidification shrinkage as well as thermally induced deformation of solid phase are accounted for.